Integration of Medical Ethics from an Islamic Perspective in Shaping Professionalism in Medical Education: A Literature Review - Amalia, St Rahmatul; Julyani, Sri; Alwi, M Khidri (Journal of Asian-african Focus in Health, 2026)
Medical education is a long-term professional education that requires students to comprehensively master academic competencies and clinical practice. Developing professionalism is a crucial aspect because it determines the quality of service and public trust in the medical profession. Medical ethics, in this process, serves as a moral and behavioral foundation, including Islamic values that emphasize trustworthiness, justice, and responsibility in healthcare. The application of these values in medical education is crucial for the holistic development of character, moral integrity, and professionalism in medical students. This study used a literature review approach by analyzing relevant publications obtained from databases such as PubMed, Research Gate, and Google Scholar. The selected literature focused on medical ethics from an Islamic perspective, professionalism, medical education, and the integration of Islamic values. This study demonstrates that Islamic medical ethics, grounded in the Qur'an, Hadith, and the principles of Sharia law (maqasid sharia), such as trustworthiness, justice, ihsan, honesty, hifz al-nafs (protection of life), and la darar wa la dirar (do not harm oneself or others), play a significant role in shaping student professionalism. Integrating these values into the curriculum, learning, and academic environment can enhance components of professionalism such as altruism, accountability, excellence, and humanism. Furthermore, the systematic application of Islamic ethical values in the educational process strengthens empathy, responsibility, and the ability to make decisions grounded in ethical principles within modern medical practice. The integration of medical ethics from an Islamic perspective is an essential strategy in medical education to produce physicians who are not only academically competent but also possess high moral integrity and professionalism and are able to provide holistic healthcare services.